A Project feasiblity study on Pestaside - Abanto, Ray Anthony; Abarquez, Joselito; Cordova, Kenneth Irving (Diliman, Quezon City College of Engineering, 2003)
For the past few decades, Filipino farmers witnessed how common field pests have greatly damaged the country's agricultural industry. Crop production has become minimal and the others that make it to the market are further reduced because of spoilage. This has affected negatively the country's capability to export its product. Farmers then, resulted to using chemical pesticides to protect their crops. It has greatly reduced the amount of damaged crops, but consequently, ts adverse effects on the environment cannot be ignored. As a result, the Integrated Pest Management (IPM) was launched. IPM is a move for the reduction of pest problems by actions selected after the life systems of the pests are understood and the ecological as well as economic consequences of these actions have been predicted, as accurately as possible, to be in the best interest of mankind. Part of the movement is a recommendation to use organic pesticides or those that come from natural sources. Thus, PestAside was conceived and a feasibility study regarding this new product was conducted. The study was concentrated on the use of an organic pesticide specifically made from Capcicum frutescens (chilly pepper) with the fruit fly as its target organism. Capsicum frutescens from local and imported sources were both considered as raw material of the product. Top fruit export products will be the leading application of the pesticide. Four aspects of the study should be reviewed in order to come up with a sound conclusion. These are the market study, technical study, financial study, and socioeconomic study. From the market study, it was found that the fruit sub-sector of the agricultural industry is stable over the next five years. Continued government initiative in the implementation of IPM in farms all over the country provided demand for PestAside. Failure by the local pesticide industry to provide organic pesticides in the market gave the product a monopoly for organic fruit pesticides. From the technical study, the method od production was determined. Between production and formulation, production was chosen . Raw materials shall be sourced locally but the machines that will be used will be imported from other countries. Facilities planning was also done. Laguna Technopark was chosen as the plant site. The plant site shall be constructed. A product layout type of facility was determined optimal for the company because of the high volume-low variety type of production. Corporation is the type of business organization that was deemed necessary for the company. The total project cost was computed and amounted to Php 38,091,224.57. From the financial study, the forms of financing were determined. Equity and loan financing were concluded to be the forms of financing for the company. Landbank Philippines was established as the institution from where the loans will come from. Tax considerations and exemptions were determined. Several financial performance measures and sensitivity analyses measures were done, which produced positive and favorable results. From the socioeconomic study, benefits to the nearby community were determined. Additional jobs were created. The raw material, machine, and tool requirements create a more stable production for suppliers. Production of the main ingredient also influenced nearby provinces for additional production of chili peppers. The community shall also benefit from the municipal and government taxes that the company shall be paying. Employee's taxes would also help the same way. From these findings, it can be concluded that the project is feasible. There exists a market for the product and technology for production is present. The financing requirements are realizable. The project is both internally and externally favorable to the company.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Pesticides; Participatory monitoring and evaluation (Project management)